Leisure Time in "Amateur" and High Level Female Gymnasts - Viviani, F.; Grassiviaro Gallo, P. (The Hong Kong Journal of Sports Medicine and Sports, 2002)
Leisure time (LT) is a complex construct determining the quality of life. It was investigated on 155 gymnasts (82 "amateurs" and 73 agonistics) aged 11.3±2.1 years by means of a questionnaire in order to gain insights on their previous sporting history, the meaning of LT for them, the quantity of their available LT and the way they used it. In the whole sample, gymnasts declared in 89.6% of the cases to have LT (which coincides with free time), even if they wanted more LT in 67.8% of the cases, in order to stay with friends (47.5%), to cultivate their favourite hobbies (26.7%), and to play (23.8%). Apart from the fact that agonistic athletes had an average half LT than the others, few differences emerged between "amateur" and agonistic gymnasts: hours spent watching television (p<.05), hours devoted to homeworks (p<.05) and parents (p<.001) and those dedicated to themselves (p<.05). The differences between the subsamples regarded the quantitative aspects instead of the qualitative ones, highlighting the fact that a substantial homologation occurred between them. For the qualitative aspects of LT gymnasts appear not to conspicuously differ from the same age Italian unpracticing girls, already investigated in previous studies.